Self Efficacy Sebagai Mediator Prestasi dan Minat BelajarTerhadap Kemampuan Praktik Tune Up Siswa SMK - Mandatama, Rico; Jatmoko, Dwi; Primartadi, Aci; Setiawan, Angga; Tubagus, Ahmad Agil (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the role of self-efficacy as a mediator in the influence of achievement and learning interest on the practical ability of engine tune-up in eleventh grade students of the Light Vehicle Engineering Expertise Program at Muhammadiyah Seputih Raman Vocational High School. This study used an ex post facto method with a population of all students totaling eighty-four students and the sampling technique was carried out saturated. The research instrument was prepared in the form of a questionnaire, then tested for validity with product moment correlation and reliability using the Cronbach's Alpha coefficient so that the instrument is suitable for use in obtaining data. The results showed that learning achievement has a positive influence on practical ability, as well as learning interest is proven to have a positive influence. Simultaneously, both variables contribute significantly to the practical ability of engine tune-up, while self-efficacy plays an important role in strengthening the relationship between learning achievement and learning interest with students' practical ability, so that the higher the self-efficacy, the more optimal the practical ability achieved..